2019
DOI: 10.1097/hcr.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Trends in Cardiac Rehabilitation: 1996-2015

Abstract: Purpose: Clinical interventions in programs such as cardiac rehabilitation (CR) are guided by clinical characteristics of participating patients. This study describes changes in CR participant characteristics over 20 yr. Methods:To examine changes in patient characteristics over time, we analyzed data from 1996 to 2015 (n = 5396) garnered from a systematically and prospectively gathered database. Linear, logistic, multinomial logistic or negative binomial regression were used, as appropriate. Effects of sex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…A follow-up study investigated how clinical characteristics of patients enrolled in CR have changed from 1996 to 2015 and found an increase in the prevalence of obesity during this time period. 65 However, no sex differences were present in BMI or frequency of obesity (as indicated by BMI) in patients at CR entry which is consistent with previous studies. 58,65,94–96 The AHA/ACC Secondary Prevention goal for weight management is a BMI of 18.5 to 24.9 kg/m 2 ; however, this goal is one of the least likely to be achieved at CR completion.…”
Section: Sex Differences In the Core Components Of Crsupporting
confidence: 91%
See 1 more Smart Citation
“…A follow-up study investigated how clinical characteristics of patients enrolled in CR have changed from 1996 to 2015 and found an increase in the prevalence of obesity during this time period. 65 However, no sex differences were present in BMI or frequency of obesity (as indicated by BMI) in patients at CR entry which is consistent with previous studies. 58,65,94–96 The AHA/ACC Secondary Prevention goal for weight management is a BMI of 18.5 to 24.9 kg/m 2 ; however, this goal is one of the least likely to be achieved at CR completion.…”
Section: Sex Differences In the Core Components Of Crsupporting
confidence: 91%
“…64 Consistent with this, females enrolled in CR generally exhibit a lower VO 2 peak before CR initiation compared with males. 57,58,65 Importantly, numerous studies have reported sex differences in VO 2 peak following CR with females having less of an improvement. [57][58][59]66 For example, Rengo et al 57 recently investigated if sex differences are present in the VO 2 peak improvement following CR programming in 1789 patients.…”
Section: Exercise Trainingmentioning
confidence: 99%
“…The Cohen weighted kappa (κw) = 0.71 similarly indicates a good agreement of these tertile rankings. 17 The demographics of our study population are similar in sex, race, weight, and BMI to recently reported larger CR cohorts (a 12 984-member CR cohort in the United States during 2000-2009 19 and a 5396-member cohort 20 in Vermont collected over 20 yr). Participants in this study reported dietary fat composition and fiber intake that are very similar to NHANES dietary intake data reported for 2015-2016 21 but, on average, reported about 300 kcal less energy intake/d and almost half the sodium intake.…”
Section: Discussionsupporting
confidence: 54%
“…Overall, the sex and age demographic distribution of the patients who participated in CR in our study is largely similar to those in previously published studies, with mean age around 65 years and women making up slightly <30% of the patient population. 30 , 31 Patients participating in CR had a high prevalence of cardiac risk factors, with an average of 5.4 physician‐identified risk factors on intake to CR, with the most common being hyperlipidemia and hypertension. In particular, we found that women had a clustering of adverse risk factors and comorbidities: women were older, had poorer control of cardiac risk factors, and were more likely to have a lifestyle with little to no regular exercise, were more likely to be obese, and had higher rates of stress than men.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of patients, about 1 in 5, came to CR after receiving cardiac valvular interventions, which reflects the increase in patients in CR with valvular interventions since the Centers for Medicare and Medicaid Services expanded CR coverage to this population in 2006. 31 , 34…”
Section: Discussionmentioning
confidence: 99%